A Quantum View of Marketing Strategies - Kaan Tuğrul Özkan; Halit Keskin (Journal of International Trade, Logistics and Law, 2020)
Businesses try to create a competitive advantage by utilizing their knowledge that has been developing for years. When firms do business with their traditional logic, they try to compete to increase their profit margins. However, competitive businesses work on what opportunities they can create in the industry, how they can keep buyers close to them in the long run, and what strategies they can develop to dominate the market. In the literature, suggestions are given to companies on how they can move away from stereotyped strategies that can stimulate one another and provide them with high-profit margins, how to create new market spaces and create leaps in the value which is perceived by the customer. After in-depth reading about these concepts in the literature, it is perceived that value innovation creates new market space and customer value and quantum marketing strategies come into consideration relevantly. This study represents particular importance to cover the shortcomings in the literature in this field.